Molecular phylogeny and morphology reveal a new wood-inhabiting fungal species, Stereum tongbiguanense (Stereaceae, Russulales) from China - Chen, Meng; Deng, Yinglian; Wang, Kaisheng; Zhu, Yonggao; Yang, Rongcong; Zhang, Shihui; Su, Qidong; Zhao, Changlin (Phytotaxa, 2025)
Taxonomy plays a central role in understanding the diversity of life, translating the products of biological exploration and discovery (specimens and observations) into systems of names that establish a “classification home” for taxa. In this study, a new species, Stereum tongbiguanense, is proposed based on the morphological features and molecular evidence. The new species is characterized by coriaceous basidiomata with smooth, white to cream hymenial surface, a dimitic hyphal system with generative hyphae bearing simple septa, and allantoid basidiospores measuring 5.4–6.8 × 2.5–3.5 µm. The phylogenetic tree inferred from ITS+nLSU sequences reveals that S. tongbiguanense is nested within the family Stereaceae of the order Russulales, forms a sister lineage with S. tropicum, and is also closely related to S. insigne. A full description, illustrations, and phylogenetic analysis results of the new species are provided.